Проблеми радіаційної безпеки авіапасажирів та членів екіпажів повітряних суден та підходи до соціально-економічних, інноваційних та правових напрямків їх вирішення - Баран, Р. Т. (Видавництво Львівської політехніки, 2015)
Розглянуто проблеми радіаційної безпеки авіапасажирів і членів екіпажів повітряних суден (ПС), оскільки вони не стали поки що предметом наукових досліджень серед тих, хто вивчає інноваційні підходи в управлінні базовими галузями економіки країни. На ці проблеми не звертають уваги ні авіапромисловці, ні авіаперевізники, що не сприяє розвитку літакобудування і розширенню авіатранспортних послуг (АТП). Відсутність у літаках вітчизняного виробництва захисних екранів від природного опромінення (ПО) гальмує інтенсифікацію їх використання на ринках світової авіатранспортної системи, не забезпечується економічна ефективність та конкурентоздатність. Запропоновано можливі підходи до вирішення цих проблем та зменшення негативного впливу ПО на споживачів АТП. Problems of radiation safety of passengers and crew of aircraft, because they have not become a subject of research as yet and have not spread among those who are exploring innovative approaches in the management of basic sectors of the economy, are investigated in this article. No attention is paid to them, neither by aviation industry nor by air carriers, does this not favor the development of aircraft construction and the expansion of air transport services (ATS). The lack of protective screens against natural radiation (NR) in aircrafts inhibits the intensification of their use in the markets of the world air transport system. Therefore, there is no economic effectiveness and competitiveness. Possible approaches to solving these problems and reduction of the negative impact of natural irradiation on consumers of ATS are suggested. Description of the object of the investigation. The problems of air transport industry and the whole transport complex in Ukraine consist in their reformation with the goal of their continuous development. And, from each point of view, these measures for development of air transport as infrastructure should be undertaken on innovative basis. For the purpose of competitiveness of operators of airplanes on external air transport markets, namely national aircraft manufacturers and companies, principles of environmental safety acquire the greatest importance. The results of research on innovative approaches to competitiveness and increase of economic efficiency as well as environmental safety of the national system of aircraft industry and air transport (airlines) are presented in this article. The relevance of the work. The article, is extremely relevant, since it offers the main approaches to the definition of socio-economic efficiency as well as the means of improvement of consumer qualities of Ukrainian aircraft with the aim of their design, manufacturing, sales and offer (transportation opportunities) in the markets of air transportation services in the world. Recently, the development of the aircraft Antonov family (An-140 up to An-178) continues. Therefore, in this the article the author's suggestions consist in design of, figuratively speaking, screens against the natural irradiation. This problem is especially relevant in air travels (flights) at the altitude of cruiser echelons. Thus, the complex security observation, ecology, and expansion of the concept of “aviation security” as well as, the increase in competitiveness and efficiency of air transport on this basis make up a scientific novelty of the article. The results consist in the fact that the author from the point of view of the aircraft operator examined the organization, design, production for the operation of the air transport market segments of distant end height routs as just for the subjects of Ukrainian air transport. Then they will be operated safely for the users and commercially effectively as made in Ukraine aircraft. And this is the urgent need in scientific – practical elaboration and decision of this problem. Value the conducted research and, specifically, its results consist in the statement of conclusions which can be used in practice of state regulation in air transport; legislative regulation of issues of ecological safety both of passengers and crews are elaborated. It is stated that in this case there are possibilities to increase efficiency, ecological safety, and competitiveness of the national air transportation system.
Problems of aircraft passengers and crews radiation safety and approaches to socio-economic, innovative, and legal directions of solving them
Keywords: радіаційна безпека авіапасажирів; природне опромінення; інновації засобів захисту членів екіпажів повітряних суден; безпека авіації; безпека польотів; безпека авіаперевезень; правове регулювання вирішення проблем природного опромінення пасажирів на повітряних суднах українського виробництва; radiation safety of air passengers; natural irradiation; innovations of means of protection for crew of aircraft; aviation safety; flight safety; aviation security; the legal regulation of issues of natural irradiation of passengers of aircraft of Ukrainian production